2019
DOI: 10.3167/sa.2019.630106
|View full text |Cite
|
Sign up to set email alerts
|

Requiem for a Waria

Abstract: This article engages recent queries in anthropology regarding where to find openings for reimagining, recreating, or rearticulating a moral and political otherwise. I suggest we can find such openings in the political potentiality of ironic experiences—intensely unnerving confrontations with the discrepancy between accepted norms and cherished ideals, of which these norms fall short. Through a person-centered account of one of Indonesia’s most well-known waria (transgender woman), I demonstrate how an out-of-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study highlights a significant increase in waria's prioritization surrounding health and welfare in their advocacy in Yogyakarta. This general move towards welfare issues, as a political strategy for gaining basic rights, provides new insights into Muslim waria's activism and their conditions of precarity since COVID-19; predominantly scholars have defined such activism through a lens of religious piety and Islamic spirituality (Thajib 2017;Tidey 2019;Kjaran and Naeimi 2022). The significance of access to food security, physical-psychological wellness, and financial stability in waria's human rights advocacy shows how Indonesian gender nonconforming citizens envision security in a rapidly-changing, modern world.…”
Section: Conclusion: Negotiating Precarity and New Modalities Of Powermentioning
confidence: 99%
“…This study highlights a significant increase in waria's prioritization surrounding health and welfare in their advocacy in Yogyakarta. This general move towards welfare issues, as a political strategy for gaining basic rights, provides new insights into Muslim waria's activism and their conditions of precarity since COVID-19; predominantly scholars have defined such activism through a lens of religious piety and Islamic spirituality (Thajib 2017;Tidey 2019;Kjaran and Naeimi 2022). The significance of access to food security, physical-psychological wellness, and financial stability in waria's human rights advocacy shows how Indonesian gender nonconforming citizens envision security in a rapidly-changing, modern world.…”
Section: Conclusion: Negotiating Precarity and New Modalities Of Powermentioning
confidence: 99%
“… On rare occasions, similar to how a waria could change their name easily or have other warias listed as kin, warias could have the sex on their identity cards changed if they had close enough relationships with local officials (Tidey 2019, 96–97). Since the 1970s, Indonesian law has permitted the sex listed on identity documents to be changed, but it requires a court case and adherence to several regulations governing the overlapping medicolegal definitions of transsexuality and intersexuality (Hegarty 2019).…”
mentioning
confidence: 99%
“…It came about when Creighton Burns , a senior lecturer in Ball's department, casually suggested that Ryan was his man. 43 Given Ryan's background in advertising and public relations, it was a surprise appointment. It was also an inspired decision to the extent that Ryan's…”
mentioning
confidence: 99%